Epidemiology of dengue disease in Malaysia (2000-2012): a systematic literature review. - Abdul Hamid Mohd-Zaki; Jeremy Brett; Ellyana Ismail; Maïna L'Azou (PLoS Neglected Tropical Diseases, 2014)
Unlabelled A literature survey and analysis was conducted to describe the epidemiology of dengue disease in Malaysia between 2000 and 2012. Published literature was searched for epidemiological studies of dengue disease, using specific search strategies for each electronic database; 237 relevant data sources were identified, 28 of which fulfilled the inclusion criteria. The epidemiology of dengue disease in Malaysia was characterized by a non-linear increase in the number of reported cases from 7,103 in 2000 to 46,171 in 2010, and a shift in the age range predominance from children toward adults. The overall increase in dengue disease was accompanied by a rise in the number, but not the proportion, of severe cases. The dominant circulating dengue virus serotypes changed continually over the decade and differed between states. Several gaps in epidemiological knowledge were identified; in particular, studies of regional differences, age-stratified seroprevalence, and hospital admissions. Protocol registration PROSPERO #CRD42012002293.